Implementation of Strategic Management in Islamic Boarding Schools: Analysis of Constraints and Solutions for Improving Education Quality - Dedi Junaedi; Elly Zumailah; Titin Sa’diah; Uus Ruswandi; Sahliah, Sahliah; Arifin, Bambang Samsul (UIN Sunan Gunung Djati Bandung, 2024)
One of the factors that play an important role in improving the quality of education isstrategic management. The purpose of this research is to find out, examine, analyse, and understand in depth about the implementation of management functions in Islamic boarding schools, factors inhibiting the implementation of management functions in Islamic boarding schools; and solutions to obstacles to the implementation of management functions in realising the goals of Islamic boarding schools Nurul Huda and At-Thaariq Garut. The method in this study uses a qualitative approach with a descriptive-holistic method and case study analysis that seeks to analyse the use of supporting tools for management practices. Based on the research results, Pondok Pesantren Nurul Huda and Pondok Pesantren At-Thaariq Garut have implemented strategic management which includes planning, directing, supervising, and evaluating, involving all divisions to achieve educational goals. However, obstacles such as lack of synergy, discipline, understanding of tasks, and conflict of orders between leaders still hinder the optimal implementation of strategies. In conclusion, to achieve better results, pesantren need to improve the analysis of HR needs, strengthen the discipline system, and conduct consistent evaluations. A collaborative and holistic approach in strategic management will help pesantren achieve their vision, mission, and expected education quality.